BHDPC Is a Novel Neuroprotectant That Provides Anti-neuroinflammatory and Neuroprotective Effects by Inactivating NF-κB and Activating PKA/CREB - Li, Chuwen; Chen, Tongkai; Zhou, Hefeng; Feng, Yu; Hoi, Maggie P. M.; Ma, Dan; Zhao, Chao; Zheng, Ying; Lee, Simon M. Y. (Frontiers in Pharmacology, 2018)
Microglia-mediated neuroinflammatory responses are inevitable and important pathological processes in several kinds of disorder of the central nervous system (CNS). Therefore, alleviating activated microglia-induced inflammatory process might be a valuable therapeutic approach to neuroinflammation-related diseases. In the present study, we investigated BHDPC, a novel neuroprotectant discovered in our previous study that had anti-inflammatory effects under neuroinflammatory conditions. First, we found that BHDPC could inhibit neuroinflammatory responses and promote microglial M2 phenotype polarization in both lipopolysaccharide (LPS)-activated BV-2 microglia l cells. Furthermore, BHDPC provided protective actions against neuroinflammation-induced neurotoxicity in HT22 mouse hippocampal cells co-cultured with activated BV-2 microglia. Further experiments demonstrated that BHDPC could suppress LPS-induced activation of transcription factor nuclear factor kappa B (NF-κB) via interfering with the degradation of the inhibitor of kappa B (IκB) and phosphorylation of IκB, the IκB kinase (IKK). Moreover, we also found that BHDPC could induce phosphorylation of cAMP-dependent protein kinase A (PKA) and cAMP-response element-binding protein (CREB) in BV-2microglial cells. Also, using the PKA-specific inhibitor, we found that BHDPC-induced CREB phosphorylation was dependent on PKA, which also contributed to BHDPC-mediated anti-inflammation and neuroprotection.